FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA TERDIDIK DI KOTA PEKANBARU TAHUN 2005-2016 - G, Karno Kristanto; Ningsih, Rahmita B; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the factors that affect the absorption of educated workers in Pekanbaru City, the development of educated labor absorption in Pekanbaru City and to find out the absorption of educated workers in Pekanbaru City. The target area of research is Pekanbaru City Riau Province. The type of data in this study is secondary obtained from the Central Statistics Agency, the Department of Labor and so on. While the data collection technique of this research is research library (library research) and field research (field research). The method of analysis used in this study is multiple linear regression. From the result of research known that the variable of PDRB (X1), UMK (X2) and investment (X3) tcount is bigger than t-table. This means that PDRB (X1), UMK (X2) and investment (X3) each have partial effect on employment in Pekanbaru (Y). All independent variables, PDRB (X1), MSE (X2) and investment (X3) together contributed to the absorption of manpower in Pekanbaru (Y) of 61.60%. This means that PDRB (X1), MSE (X2) and investment (X3) affect employment in Pekanbaru City. The remaining 38.40% influenced other factors not examined in this study. It is recommended that local governments should seek to expand employment opportunities, especially in sectors that can absorb more labor, pay attention to regulations in the process of developing new business that is easy, transparent and mutually beneficial to the government and investors. And create socio-economic and political stability that can affect the size of the investment.Keyword: Employment Absorption, Educated Labor